Evaluation of soybean RIL population for charcoal rot resistance: Evaluation of soybean RIL population for charcoal rot resistance - VENNAMPALLY NATARAJ; SANJEEV KUMAR; LAXMAN SINGH RAJPUT; SHIVAKUMAR M; RAJKUMAR RAMTEKE; VANGALA RAJESH; MILIND B RATNAPARKHE; SUBHASH CHANDRA; GYANESH KUMAR SATPUTE; SANJAY GUPTA (Journal of Oilseeds Research, 2020)
Charcoal rot disease caused by Macrophomina phaseolina (Tassi) Goid. is a major threat to soybean production. Identification of resistant sources and their deployment in resistance breeding programs is the best way to tackle this disease. Current study aimed to screen 125 Recombinant Inbred Lines (RILs) derived from the cross JS-97-52 × JS90-41 for charcoal rot resistance using cut-stem inoculation technique. Out of 125, 21 lines were found to be resistant compared to the better parent JS-97-52. These lines would further be confirmed for their resistance under field condition for their utilization in charcoal rot resistance breeding program.